Analysis of antibiotic use, biosecurity and mortality in semi-intensive broiler farms in Kenya - Kemunto, Naomi P.; Muloi, Dishon M.; Ibayi, Eugine L.; Njaramba, Jane K.; Hoffmann, Vivian; Murphy, Mike; Nielsen, S.S.; Moodley, Arshnee (BioMed Central, 2025)
The indiscriminate use of antibiotics in food-producing animals contributes to antimicrobial resistance (AMR), posing a global threat. Understanding the factors associated with antibiotic use is critical to combat resistance while maintaining animal health. This study examined antibiotic use practices, mortality rates, biosecurity levels, as well as the associations between biosecurity and antibiotic use, and between biosecurity and mortality, in semi-intensive broiler farms in Kenya.